The Development of Learning Media on Building Three-Dimensional Shape using E-Comic - Fitriani, Nelly; Ronny, Renata Teddy (IKIP Siliwangi, 2025)
The importance of the teacher's role in increasing students' interest and motivation in learning mathematics is that one of the steps taken is using interactive learning media in the form of E-Comic supported by the RME (Realistic Mathematics Education) learning approach. Using E-Comic in mathematics lessons can summarize the material and present it interestingly. This study aims to describe the development of learning media using E-Comic, students' responses to E-Comic on cylindrical geometry material, and the process of developing E-Comic. This study is an RnD (research and development) study using the ADDIE model with four stages, namely analysis, design, development, and implementation. The subjects of this study were 30 junior high school students and 3 validators as media experts and material experts. The object of this study is the learning media for cylindrical geometry using E-Comic with the RME approach with the help of the Canva application. The data collection tools used were validation sheets and student response questionnaires. The response questionnaire was closed and contained eight questions. The results of this study indicate an average validation of the E-Comic media of 80% with a very valid category. At the same time, the average student response results were 87% with a very practical category. From the results obtained, the E-Comic learning media with the RME approach is very valid and practical to use in the learning process and can increase students' interest and motivation to learn about the material on cylindrical spatial structures.